Penerapan Asas Kelangsungan Usaha Debitor Pailit (Studi Kasus Putusan Nomor 10/Pdt.Sus-Pailit/2024/PN.Niaga.Smg) - Putri, Nadila Azzahra (Wajah Hukum, 2025)
This study aims to explore the concept of Going Concern in the context of bankruptcy and analyze how this principle is applied in bankruptcy law. The going concern principle provides an opportunity for potentially viable debtor companies to continue operating. The provision in Article 104 paragraph (1) of Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (UUK-PKPU) stipulates that the curator has the authority to continue the business activities of the debtor declared bankrupt, provided that they obtain approval from the temporary creditors' committee or permission from the supervisory judge if the creditors' committee is not formed. The filing of a bankruptcy petition can be done by the debtor or creditor with relatively easy requirements, namely having at least two creditors and debts that are due and collectible, as stipulated in Article 2 paragraph (1) of Law Number 37 of 2004. (UUK-PKPU). The easy requirements often harm the debtor, as they can be exploited by a bankruptcy applicant with bad intentions. As in the Commercial Court Decision Number 10/Pdt.Sus-Pailit/2024/PN.Niaga.Smg, where the panel of judges declared PT Panamtex bankrupt based on the minimum requirements for a bankruptcy petition and did not consider the solvency condition of the company. Therefore, can the principle of business continuity still be present in providing protection for the debtor, and how is it applied when viewed from the perspective of bankruptcy law in Indonesia.